Gross testicular abnormalities in indigenous breeds of bulls in Eastern Ethiopia - Gemeda, Amare Eshetu (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This study was conducted to assess the prevalence of different types of gross testicular disorders in bulls, and to evaluate the associations with sampling year, age, and body condition. Materials and methods: In this study, a total of 398 apparently healthy bulls were randomly selected that were brought from different parts of eastern Ethiopia to the Haramaya University abattoir for slaughtering during the period from June 2014 to September 2016. Ante- and post-mortem examinations of the bulls were employed. Visual inspection, palpation, serial and systematic dissections into the parenchyma of the testes and scrotum were performed to determine the presence and the extent of gross pathological changes. Results: Out of 398 bulls, 209(52.5%) were affected by one or more gross testicular abnormalities of unidentified causes. Bilateral testicular hypoplasia was the most prevalent (9.8%; n=39/398) testicular abnormality, followed by unilateral testicular hypoplasia (9%; n=36/398), testicular hematoma (9%; n=36/398), orchitis (8.3%; n=33/398), testicular degeneration (6.5%; n=26/398), scrotal wound (6.3%; n=25/398) and epididymitis (2.5%; n=10/398). Unilateral cryptorchidism was the least prevalent (1%; n=4/398). Age and body condition did not affect the prevalence of any abnormality (P>0.05) except in scrotal wound which was significantly varied among body condition categories (P<0.05). Conclusion: This study reveals that the incidence of gross testicular abnormalities was 52.5% in bulls. Thus, attention should be given to reproductive management of bulls in Ethiopia. http://doi.org/10.5455/javar.2017.d201 XML PubReader